The Effects of Management Information System toward Decision Making in Food and Beverage Service Department in X Resorts and Hotels Bandung - Agung Gita Subakti; Maria Pia Adiati (Binus Business Review, 2015)
In an organization, decision making hold an important role. That is why a decision made by managers should be a final decision that should be done by their subordinates or those who are related with the organization. In the effort to increase the quality of management information system, a research was held in X Resorts and Hotels Bandung to analyze management information system in the relation to decision making especially in Food and Beverage Service Department and recommendation of how to handle the problem occurred. From the questioner with data analyzing technique of spearman rank gained correlation result 0,84, with determination coefficient 71% which means the management information system has 71% level of influence to decision making, meanwhile the rest of the result (29%) shows other factors, which also were related with the decision making other than management information system. To solve with the problem, it is recommended that X Resorts and Hotels decrease the level of information product error in management information used and fasten the delivery of provided information.